DEVELOPMENT OF TRAINING CURRICULUM TO ENHANCE THE ABILITY OF COMPETENCY - BASED LEARNING MANAGEMENT DESIGN FOR HEALTH EDUCATION TEACHERS - Phroedphring, Chatchana; Sarayuthpitak, Jintana; Tingsabhat, Suthana; Rodpipat, Sarinya (Academic Journal of Thailand National Sports University, 2023)
This research aim was to propose a training curriculum to enhance the ability of competency - based learning management design of health education teachers. The research process was divided into 4 steps: Step 1: Study the background information by interviewing experts and synthetic analysis of textbooks and literature review on training curriculum in order to enhance the ability of competency - based learning management design of health education teachers. Step 2: Study the concepts and theories used to create training courses that improve the abilities of health education teachers’ competency - based learning management. Step 3: Create training courses. Step 4: Check the quality of training courses by 5 experts who examine the quality of the curriculum in 2 areas: 1) The suitability of the curriculum by using an evaluation form; 2) The consistency of the curriculum by using a 5 - level estimator questionnaire The results showed that the training course consisted of the following components: 1) Principles and background 2) Objectives 3) 5 learning units, each unit consists of (1) Main points (2) Learning management objectives (3) Learning subjects (4) Learning management process (5) learning media and resources and (6) Measurement and evaluation methods. 4) The activities used 5) Training course duration 6) Media used 7) Evaluation and 8) Training plans. The duration of training was 3 days. The result of the qualifying examination on the suitability of the training course was a total mean of 4.45, and the consistency index of the training course was 0.95, which were very appropriate to be used.